PROPOSED DIGITAL MARKETING STRATEGY FOR LEAD GENERATION IN B2B SAAS INDUSTRY: (A CASE STUDY OF EMPLORAX IN SINGAPORE) - Sukraj Putera; Novika Candra Astuti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The Software-as-a-Service (SaaS) business-to-business (B2B) industry in Singapore faces much difficulty in acquiring qualified leads and then converting them in environments with risk averse and multi stakeholder purchasing decisions. The present study examines how Emplorax an imaginary name for a Singapore-based SaaS firm may digitalize its marketing strategy and raise leads quality, conversion, and marketing return on investment (ROI). The study is a paradigm mix of qualitative and quantitative methodologies through the integration of data from CRM systems, advertisements dashboards as well as websites analytics, with the qualitative insightes coming from internal interviews. A strategic framework outlines the analysis, which includes both external and internal diagnostics, funnel-based channel mapping, and performance optimization levers. The results demonstrate the clear differences in the performance of the channels. SEO and Google Ads can offer along with the lowest cost per lead the highest number of leads and conversely, Meta Ads affect the pipeline quality the least. Internally, critical limitations appear in CRM segmentation, mid-funnel email automation, and the lack of performance feedback loops. Particular market limitations such as stringent procurement procedures and the need for integration readiness further decrease the conversion rate. The proposed approach is the introduction of two sequential executions' playbooks. Playbook A deals with Capture and Qualify Leads through Digital Acquisition. Besides, Playbook B will meet the conversion with the help of retargeting offline engagement and the structured sales follow-up, which is tagged for high-intent leads identification. The scheme also proposes standardizing CRM lifecycle, automating nurture workflows, and using multi-touch attribution modeling, specifically for the Singapore context. This thesis shows a realistic plan for SaaS marketers, who are working in high-consideration B2B environments. By employing a data driven, funnel aligned strategy accompanied by structured playbooks, the companies will be enabled to improve lead qualification, pipeline velocity, and marketing-to-sales collaboration. The framework is a remediable model for regional SaaS companies, which are willing to perform through digital marketing integrated.